1999
DOI: 10.2337/diacare.22.11.1851
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the intima-media thickness of the carotid artery and aortic pulse-wave velocity in patients with type 2 diabetes. Vessel wall properties in type 2 diabetes.

Abstract: The results indicated that diabetic patients showed more advanced changes in atherosis than that in sclerosis as compared with age- and sex-matched control subjects. Such atherotic changes in diabetic patients may be associated with hyperlipidemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
213
7
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(254 citation statements)
references
References 0 publications
27
213
7
7
Order By: Relevance
“…Strong positive correlation of intima-media thickness with carotid-femoral PWV has been observed in large population cohort studies 27 and in patients with diabetes. 19,40 baPWV 16,17 was also useful to predict the early stages of atherosclerosis. 18,19 In contrast, Nishi et al 41 also observed a significant but poor correlation between baPWV and intima-media thickness in subjects with diabetes and no significant relationship with baPWV in the presence of plaques.…”
Section: Macroscopic and Microscopic Findings Of The Aortamentioning
confidence: 99%
“…Strong positive correlation of intima-media thickness with carotid-femoral PWV has been observed in large population cohort studies 27 and in patients with diabetes. 19,40 baPWV 16,17 was also useful to predict the early stages of atherosclerosis. 18,19 In contrast, Nishi et al 41 also observed a significant but poor correlation between baPWV and intima-media thickness in subjects with diabetes and no significant relationship with baPWV in the presence of plaques.…”
Section: Macroscopic and Microscopic Findings Of The Aortamentioning
confidence: 99%
“…4 There is now established evidence that aortic stiffness increases with aging and prolonged elevation of blood pressure, 5 and is the underlying pathology of isolated systolic hypertension. 6 Aortic stiffness is closely associated with cerebral large-arterial disease involving the extracranial internal carotid [7][8][9] and intracranial large arteries. 10 It is not possible to study the direct association of aortic stiffness with changes in cerebral microvessels, which cannot be routinely assessed with current imaging technology.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research has established carotid intimamedia thickness (CIMT) as a clinical surrogate marker of atherosclerosis [3]. Although pulse wave velocity values can be roughly correlated with CIMT [3], when assessing pulse wave velocity in clinical practice, confounding factors such as abnormalities of blood pressure (BP), blood flow and sympathetic tones might increase the variability of pulse wave velocity [4] that is often observed in subjects with obesity and type 2 diabetes.…”
mentioning
confidence: 99%